Infection Prevention Control (IPC), Hospital acquired infection (HAI) and Obstetrics practice - Baral, Reetu (Nepal Journal of Obstetrics and Gynaecology, 2022)
Infection prevention and control program is important to prevent infectious morbidity. Simple method like hand washing to effective sterilization methods are recommended in clinical practice. Immunocompromised state of pregnancy and newborn are more vulnerable to acquire infection; and there is a real challenge from hospital acquired infection because of surgical nature of obstetric care.